Computer assisted optimisation on non-pharmacological treatment of congestive heart failure and supraventricular arrhythmia - Reumann, Matthias (Karlsruhe transactions on biomedical engineering, 2007)
Heart Failure is the most common cardiac disease worldwide; supraventricular arrhythmia the most common cardiac arrhythmia. The understanding of these diseases advances treatment options. Ablation therapy and atrial antitachycardial pacing are non-pharmacological options in the treatment of atrial fibrillation. Cardiac resynchronization therapy with biventricular pacing devices has been shown successful in patients with severe heart failure. However, an optimization or even individual therapy planning is not standard or not even carried out today.